Malaysia Legislates the Rights of the Child: Challenges, Progress and Impact - Zakaria Mohd Kawi; Asmady Idris; Abdul Said Ambotang; Mansoureh Ebrahimi (Sciendo, 2022)
Since the adoption by the United Nations in 1989 of the Convention on the Rights of the Child, all the 196 States including Malaysia have agreed to be bound by the treaty which simultaneously ushers the beginning of the new era in legislating the rights of the child based on binding norms that are now universally applicable.Hence, the paper intends to examine the status of Malaysia`s reservations, the challenges it has been facing in the light of its reservations, reporting requirements, and the international human rights monitoring procedure in implementing legislation concerned with the Child Act 2001. For the research methodology, the study applies International Law, Reservation and Convention and will analyse empirical materials including primary reports from the United Nations, the Malaysian government and non-government agencies. The paper concludes that Malaysia will continue to stride towards a humanely progressive promulgation of all the rights enshrined in the Treaty